Trends and Dilemmas in the Utilization of Renewable Energy Sources - Posza, Barnabás; Borbély, Csaba (Acta Scientiarum Socialium, 2015)
Trends and Dilemmas in the Utilization of Renewable Energy Sources.Due to the efforts in the interests of achieving the sustainable development several legislation have been born supporting the utilization of the renewable energy sources and within that the usage of biomass as a conditionally renewable energy source. At the time of creation of the directives there were less available practical experience. After consulting the studies published in our country and abroad in this line in this article we presented the changes of attitudes and opinions due to the expansion of knowledge. The purpose of this study is to present the local and global consequences of em-phasizing the utilization of the biomass as a conditionally renewable energy source and how much does it affect the fulfilment of the originally set goals.To prepare the study we used international and national publications as well as legal and statistical data published by the European Union and the United Nations on this subject.
Keywords: sustainability; renewable energy; biomass; by-product; land use